Toxicity testing of some essential oils on Tetranychus urticae Koch (Acari: Tetraychnidae) and Predator Spider Phytoseiulus persimilis Athias-Henroit (Acari: Phytoseiidae) - Aissaoui, Asmae Bakkali; Elamrani, Amal (Journal of agricultural, environmental and veterinary sciences, 2020)
The essential oils of the three aromatic plants, Mentha pulegium, Thymus capitatus and Origanum compactum, are toxic to agricultural pests. This experiment was carried out with the aim of testing toxicity by direct contact with these essential oils, under laboratory conditions, on adult individuals of Tetranychus urticae Koch (Acari: Tetranychidae) and predator spider Phytoseiulus persimilsi Athias-Henroit (Acari: Phytoseiidae) which is one of the most important natural enemies of this pest. The residual activity of these essential oils has also been tested. The oil preparations were prepared for the study according to increasing concentrations: 0.5, 1, 2, 4 and 8% of each essential oil. The results showed the following:All the tested essential oils showed high toxicity towards the adult individuals of T. urticae, but pennyroyal and thyme oil are more effective than oregano oil. We obtained 100% total mortality at a concentration of 1% in the case of pennyroyal and thyme versus 84.99% in the case of oil oregano. Also, the residual activity of these oils decreases over time.On the other hand, these oils are less toxic to adult individuals of P. persimilis. At a concentration of 1% of pennyroyal, thyme and oregano oil, mortality ratios estimated at: 44.94, 16.82 and 6.9% respectively.Conclusion: These results indicated that these essential oils may represent a promising alternative to synthetic pesticides on the horizon of developing biological pest control within integrated control programs as the best and safe option for human health and the environment in general.
Keywords: spider mites; predatory spider; essential oils; pennyroyal; thyme; oregano